Student MENTAL HEALTH & WELLBEING IN HIGHER EDUCATION : A practical guide - Barden, Nicola, ditor; Caleb, Ruth, ditor (Thousand Oaks, California : Sage, 2019)
Good mental health is essential for students to manage the challenges that university life presents. This book offers pragmatic guidance to support academic and student services staff in engaging with this critical issue, both in terms of being proactive within their role to promote a positive approach to wellbing, and understanding how to care appropriately for students who may not be flourishing in the university environment--back cover.